THE EFFECT OF TEACHER PERLOCUTIONARY ACTS TO STUDENTS REACTION IN CLASS DURING LEARNING PROCESS AT 7th GRADE OF SMPN 2 KESU’ - Lois Tandi Liling (Teaching English as a Foreign Language Overseas Journal, 2022)
The main objective of the research is to find the types of perlocutionary acts use by teacher in class and the effects of teacher perlocutionary acts to students during learning process at SMPN 2 Kesu’. In analyzing the data of this research, the researcher employed qualitative method. The writer used the Miles and Huberman model analysis. The population is the 7th grade students at SMPN 2 Kesu’ and an English teacher. The writer records the data that had been obtained. The data summarized with use data reduction in order to facilitate the next step of the writer to continue the research. After the data is reduced, the data presentation presented with narrative text and then draws conclusions. The result from this study show there are four types of Searle’s speech act during learning process types of teacher perlocutionary acts in class: directive speech acts in class is command, advice, asking a question, motivation, persuasive, prohibiting, reminding, request. Representative speech acts in class are assertion, description, statement, informing. Expressive speech acts are appreciating, greeting, criticizing, and thanking. Commisive speech act is promising. The reaction of the students as the effect of Austin theory is hearer feel annoyed, hearer is caused by speaker, hearer feel alarmed, hearer feel inspired, hearer do something, and hearer realize something. Conclusion based on the research findings and discussion, the writer finally extends the conclusion about types of perlocutionary acts and the effect for the students during learning English in class at 7th grade of SMPN 2 Kesu’ is writer found four types of perlocutionary acts and six perlocutionary effects.